Applicability of qualified public key infrastructure in Ukraine - Melashchenko, A.O. (PROBLEMS IN PROGRAMMING, 2025)
The paper-founded approach to the construction of the National System of digital signatures based on the EU regulatory framework. Describes the business algorithms using digital signature as "anchor" of trust. Analyzed the degree of integration of digital signature based on the regulatory framework of the EU, modern office suites, as basic tools of e-business services.Prombles in programming 2011; 3: 79-86